آیات النصح والإرشاد في الأخلاق في سورة البقرة ( دراسة وتحلیل ) (Journal of the College of Education for Women, 2019)
This Research on (Ayat of Advice and Guidance of MoralsIncluded in Sorat Al-Baqara) is a study for the virtual of Ayatdealing with advice and guidance.The importance of this research title comes from the study ofthe Holy Quran from one side and the importance of advice andguidance from the other side, besides, we are truly in need forsuch study in our life.